Compensation of Single-Phase and Three-Phase Voltage Sag and Swell Using Dynamic Voltage Restorer - Haniyeh Marefatjou; Mohammad Sarvi (International Journal of Applied Power Engineering (IJAPE), 2012)
DVR is a equipment which was connected in series and adjusting the  loading  voltage  by  feeding  the  voltage  in  system. The  first  installation  was  in 1996. usually DVR  installed  between  sensitive loads feeder and  source in distribution system .The  main  duty, fast support load voltage  (by  fast  detection  algorithm)  during  disturbance  to  avoid  any  disconnection. in this paper approaches to compensate for voltage sag and swell as a common disturbance in voltage transmission and distribution networks is presented. A dynamic voltage restorer based on the dq0 algorithm for three-phase and dynamic voltage restorer based on the average detection method for single-phase are discussed, also in this paper we compare the two methods used to compensate the single-phase and three-phase process. result  of   three-phase and single-phase voltage sag and swell  simulation  has  been  presented  by  MATLAB/SIMULINK.